Hero’s Journey Analysis in Wish Movie (2023) - Chintya Virgianti; Ely Nurmaily (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to analyze the stages of the hero’s journey theory within the Wish (2023) movie by highlighting hope, moral courage, and the power of emotions that drive change to people as the main strength of the heroism. It also aims to determine the presence of each stage as formulated by Joseph Campbell. Using a descriptive qualitative method, this research focused on Asha, the main character, and her transformation through the narrative structure. The data were collected through careful observation of the movie, transcribing relevant scenes, and identifying each stage based on Campbell’s seventeen-stage model. The findings reveal that Asha’s journey completed all the steps in the departure stage such as the call to adventure, refusal of the call, supernatural aid, the crossing of the first threshold, the road of trials, and apotheosis. However, Asha passed four steps in initiation stage which are the road of trials, meeting with the goddess, apotheosis, and the ultimate boon. In the return stage, she only passed several steps which are crossing the return threshold, master of two worlds, and freedom to live. Despite this, Asha’s development and her efforts to bring back hope to the people of Rosas make her journey qualify as a hero’s journey.